Evaluasi Pembelajaran Tematik Terpadu Menggunakan Model Charlotte Danielson Pada Kelas III SD - Diyas Sri Widiastuti; Mawardi Mawardi (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to evaluate teacher performance in implementing integrated thematic learning in class III (three) at SD Negeri Tingkir Lor 01. Tingkir. This type of research is evaluative research. This research uses Charlotte Danielson’s model which evaluates teacher performance with 4 domains. Data validity test was done by triangulating data sources and triangulating methods. Research results : (1) Teacher’s performance in Domain1 of Learning Planning and Preparation is in the category of good with 73%, (2) Teacher’s performance in Domain 2 of Classroom Management is in the very good category with 84%, (3) Teacher’s performance in Domain 3 of Learning Process is in the very good category with 78%, and (4) Teacher’s performance in Domain 4 of Teacher Professional Responsibility is in the very good category with 78%.